Activity Patterns and Habitat Use of Northern Bobwhite Females in 2 Grazing Systems - R. Montague Whiting Jr.; Denise L. Sloan (National Quail Symposium Proceedings, 2017)
During spring and summer of 1985 and 1986, we investigated activity patterns and habitat use of female northern bobwhite (Colinus virginianus) on 2 sites in south Texas. One site had been subjected to a short duration grazing (SDG) system and the other to a continuous grazing (CG) system. Nineteen females were radio-tagged in 1985 and 28 in 1986. Rainfall was above average in 1985 and below average in 1986; as a result, herbaceous ground cover was more dense in 1985 than in 1986. Due to extensive fencing, 58% of the SDG cell was within 25 m of a mowed roadside, fencerow, or pipeline right-of-way; the same was true for 30% of the CG pasture. There were no differences (P > 0.05) in distances moved between successive locations or in the breeding season home range sizes of females in the 2 systems. In 1985, females preferred zones within 25 m of mowed areas and avoided those 50 m from such areas. In the SDG cell during 1986 only, females preferred recently grazed paddocks. The results suggest that the most important difference between the 2 grazing systems was the increased proportion of mowed areas in the SDG cell during the abnormally wet year. In the Texas Coastal Bend, landowners unable to adjust stocking rates during wet years should consider mowing to improve bobwhite habitat.
Keywords: Colinus virginianus; grazing; habitat; northern bobwhite; short duration grazing; Texas Coastal Bend